Toxicokinetics and toxicodynamics of plastic and metallic nanoparticles: A comparative study in shrimp. (1st November 2022) - Zhu, Xiaopeng; Teng, Jia; Xu, Elvis Genbo; Zhao, Jianmin; Shan, Encui; Sun, Chaofan; Wang, Qing
Abstract: Nanoplastic is recognized as an emerging environmental pollutant due to the anticipated ubiquitous distribution, increasing concentration in the ocean, and potential adverse health effects. While our understanding of the ecological impacts of nanoplastics is still limited, we benefit from relatively rich toxicological studies on other nanoparticles such as nano metal oxides. However, the similarity and difference in the toxicokinetic and toxicodynamic aspects of plastic and metallic nanoparticles remain largely unknown. In this study, juvenile Pacific white shrimp Litopenaeus vannamei was exposed to two types of nanoparticles at environmentally relative low and high concentrations, i.e., 100 nm polystyrene nanoplastics (nano-PS) and titanium dioxide nanoparticles (nano-TiO2 ) via dietary exposure for 28 days. The systematic toxicological evaluation aimed to quantitatively compare the accumulation, excretion, and toxic effects of nano-PS and nano-TiO2 . Our results demonstrated that both nanoparticles were ingested by L. vannamei with lower egestion of nano-TiO2 than nano-PS. Both nanoparticles inhibited the growth of shrimps, damaged tissue structures of the intestine and hepatopancreas, disrupted expression of immune-related genes, and induced intestinal microbiota dysbiosis. Nano-PS exposure caused proliferative cells in the intestinal tissue, and the disturbance to the intestinal microbes was also more serious than that of nano-TiO2 . The results indicated that the effect of nano-PS on the intestinal tissue of L. vannamei was more severe than that of nano-TiO2 with the same particle size. The study provides new theoretical basis of the similarity and differences of their toxicity, and highlights the current lack of knowledge on various aspects of absorption, distribution, metabolism, and excretion (ADME) pathways of nanoplastics. Graphical abstract: Image 1 Highlights: Nano-PS and nano-TiO2 exposure inhibited the growth of shrimps. Nano-PS and nano-TiO2 stimulated the expression of immune genes in hepatopancreas. Nano-PS exposure led to cell proliferation in intestinal tissue. The effect of nano-PS exposure on intestinal tissue was more serious than nano-TiO2 .